PERANCANGAN SISTEM INFORMASI KEPEGAWAIAN BERBASIS WEB MENGGUNAKAN ALGORITMA ADVANCED ENCRYPTION STANDARD (AES)-256 DI PT BERSIH SUKSES SEJAHTERA - Hanifah Adhiya; Dani Yusuf; Siti Setiawati; Hendarman Lubis (Journal of Information System, Applied, Management, Accounting and Research, 2026)
The employee data management at PT Bersih Sukses Sejahtera is still carried out using Microsoft Excel in spreadsheet form, which has the potential to cause recording errors, data duplication, delays in information retrieval, and increase the risk of employee data leakage and loss. This study aims to design an integrated web-based employee information system by implementing the Advanced Encryption Standard (AES)-256 security algorithm to improve data management security. The method used is Waterfall which includes the stages of planning, requirement analysis, design, implementation, testing, deployment, and maintenance. Data collection techniques are carried out through observation, interviews, and literature studies, while the research data includes employee data, positions, departments, training, and educational history. The system was developed using the PHP programming language and MySQL database. The results of the study show that the system is able to integrate employee data management in one platform, while the implementation of the AES-256 algorithm successfully secures URL parameters in the employee data module through encryption and decryption processes. Testing using the Black Box Testing method on 15 features obtained a 100% success rate, so that all system functions run according to user needs. Thus, the developed system is able to support structured personnel data management while increasing information security and confidentiality through the application of the AES-256 algorithm.